The first Portuguese National Health Examination Survey (2015): design, planning and implementation - Nunes, Baltazar (2019)
Background: In Health Examination Surveys interview information is complemented with objective information, providing more accurate indicators than self-reported data. We report the study design, planning and implementation of the first Portuguese Health Examination Survey (INSEF). Methods: INSEF was a cross-sectional population-based study representative at regional and national level. Individuals aged between 25 and 74 years old, residing in Portugal were selected from the national health users’ registry through multi-stage stratified probabilistic sampling. Sample size was set at 4200 individuals. Data was collected in primary care units and included blood pressure, height, weight, hip and waist measurements, blood collection for lipid profile, HbA1c and blood count and a general health questionnaire. European HES procedures were followed. Results: A total of 4911 individuals agreed to participate (43.9% participation rate). Participation rate varied by region, sex and age group, being lower in Lisbon and Tagus Valley (32.8%), for men (41.8%) and for those aged 25–34 years old (36%). Conclusions: INSEF has set up an experienced national and regional structure for HES implementation. Nationally representative quality epidemiological data is now available for public health monitoring, planning and research.